The Implementation of Cooperative Script Technique to Improve the Students’ Speaking Skill - Musfirah Musfirah; Ahmad Munawir; Fajriani Fajriani; Ridwan Ridwan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The objective of this study was to find out whether the implementation of the Cooperative Script technique could improve students’ speaking skills at SMA Negeri 3 Majene of second grade students. The method used in this study was quantitative research through a quasi-experimental design. The population was the social second grade students of SMA Negeri 3 Majene. There was XI IPS 1 as the experimental class and XI IPS 2 as the control class. The sample used for the research consisted of saturated sampling, consisting of two classes: XI IPS 1 and XI IPS 2. The result of this research shows that the Cooperative Script technique has a positive result in improving students’ speaking skills. It can be proven by the students’ average scores from pre-test and post-test. It means that the Cooperative Script technique has a significant effect on students’ speaking skills. It proved by the result of the testing Independent Sample T-test with the value of Sig. (2-tailed) was 000,0 < 0,05. It can be concluded that Ha means Cooperative Script technique has significance effect to improve students’ speaking skill was accepted and H0 means Cooperative Script technique has no significance to improves students’ speaking skill was rejected. Then, the results of the questionnaire analysis regarding students’ perception of the Cooperative Script technique, it showed that most students agreed that Cooperative Script technique makes them more active and easier to express opinions during the learning process, in this case helps students in speaking English.